The Path Assigned Mean Shift Algorithm: A New fast Mean Shift Implementation For Colour Image Segmentation. - KOKARAM, ANIL CHRISTOPHER (My University, 2008)
This paper presents a novel method for colour image segmentation derived from the mean shift theorem. When applied to colour image segmentation tasks, the path assigned mean shift algorithm performed 1.5 to 5 times faster than existing fast mean shift methods such as the Hierarchical ?Neighbourhood Consistency? FMS Method proposed by Zhang [1] with comparable results. The complexity of the new PAMS algorithm can be represented as O(2) where represents the total number of unassigned points per iteration of the algorithm.
International Conference on Image Processing (ICIP'08)
PUBLISHED
Keywords: Mean Shift, Fast Mean Shift, Colour Image Segmentation, Path Assigned Mean Shift